Genuine students as partners: How a Teaching Assistant Consultant program put students as partners into practice - Gourlay, Gerry; Korpan, Cynthia (International Journal for Students as Partners, 2018)
In this case study, a graduate student and staff member show how an institution wide program, aimed at enhancing learning and teaching in higher education, exemplifies Matthews’s (2017) “Five Propositions for Genuine Students as Partners Practice” at the department level. To do so, we describe the five propositions in relation to the Teaching Assistant Consultant (TAC) program that positions a graduate student leader in each department to support new Teaching Assistants (TAs). Through comparison, we look at how the program is inclusive, exhibits strong power-sharing capabilities through continual reflection and conversation, is ethical, and is strongly transformative.